Comparative Proteomic Analysis of Polarized Human THP-1 and Mouse RAW264.7 Macrophages - Li, Pengfei; Hao, Zhifang; Wu, Jingyu; Ma, Chen; Xu, Yintai; Li, Jun; Lan, Rongxia; Zhu, Bojing; Ren, Pengyu; Fan, Daidi; Sun, Shisheng (Frontiers in Immunology, 2021)
Macrophages can be polarized into classically activated macrophage (M1) and alternatively activated macrophages (M2) in the immune system, performing pro-inflammatory and anti-inflammatory functions, respectively. Human THP-1 and mouse RAW264.7 cell line models have been widely used in various macrophage-associated studies, while the similarities and differences in protein expression profiles between the two macrophage models are still largely unclear. In this study, the protein expression profiles of M1 and M2 phenotypes from both THP-1 and RAW264.7 macrophages were systematically investigated using mass spectrometry-based proteomics. By quantitatively analyzing more than 5,000 proteins among different types of macrophages (M0, M1 and M2) from both cell lines, we identified a list of proteins that were uniquely up-regulated in each macrophage type and further confirmed 43 proteins that were commonly up-regulated in M1 macrophages of both cell lines. These results revealed considerable divergences of each polarization type between THP-1 and RAW264.7 macrophages. Moreover, the mRNA and protein expression of CMPK2, RSAD2, DDX58, and DHX58 were strongly up-regulated in M1 macrophages for both macrophage models. These data can serve as important resources for further studies of macrophage-associated diseases in experimental pathology using human and mouse cell line models.